2019
DOI: 10.1039/c9nr07425b
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetization of immobilized, weakly interacting, superparamagnetic nanoparticles

Abstract: A theory for the magnetic properties of interacting immobilized superparamagnetic nanoparticles with various distributions is tested against simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 54 publications
(90 reference statements)
0
25
0
Order By: Relevance
“…This approach is also verified by the analytical calculations for super-paramagnetic particle magnetisation. 94 The long range magnetic interaction and the Zeeman coupling for super-paramagnetic monomers are accounted for just as they are for ferromagnetic monomers, see eqn (3) and (4), respectively.…”
Section: Main Interactionsmentioning
confidence: 99%
“…This approach is also verified by the analytical calculations for super-paramagnetic particle magnetisation. 94 The long range magnetic interaction and the Zeeman coupling for super-paramagnetic monomers are accounted for just as they are for ferromagnetic monomers, see eqn (3) and (4), respectively.…”
Section: Main Interactionsmentioning
confidence: 99%
“…For weakly interacting systems (w L t 0.5), we expect U N = 0 when starting with sufficiently random positions, 30 whereas U N E 0.5 was found in the low-temperature regime in an earlier study where particles occupy randomly the sites of a regular lattice for volume fractions f o 0.5 and l = 1. 48 These authors found that dipolar interactions can lead to U N 4 0 also in the high-temperature regime.…”
Section: Brownian Relaxation For Rigid Dipoles (Rbd Model)mentioning
confidence: 69%
“…29 In principle, eqn (2) should be supplemented by the magnetic anisotropy energy Kv m (u i Án i ) 2 due to deviations of the magnetic moment direction from the particle's easy axis orientation n i , where K is the anisotropy constant of the magnetic material and v m the volume of the magnetic core of the nanoparticle. 10,18,30 Here, we consider MNPs that are sufficiently large with a correspondingly large magnetic anisotropy energy Kv m that magnetic moment and easy axis can be considered to be well-aligned. For iron oxide nanoparticles, K E 10 4 J m À3 , this means we consider magnetic core diameters larger than 12 nm, so that k = Kv m / k B T \ 2 at room temperature, whereas for cobalt nanoparticles, K E 2 Â 10 5 J m À3 , already magnetic core diameters greater than 5 nm lead to k \ 3.…”
Section: Model Formulationmentioning
confidence: 99%
“…Motivated by a recent study of the magnetic properties of immobilized superparamagnetic particles [4], this work was devoted to the influence of the anisotropy in one-dimensional spin models with long-range dipolar interactions. Various theories were tested against computer-simulation results for the initial susceptibility and the magnetization curve.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand how the anisotropy and the orientational distribution of easy axes affect the magnetization curve and initial magnetic susceptibility of immobilized superparamagnetic nanoparticles, in order that new materials can be developed and exploited for technological applications [2,3]. Recently, this problem was studied using a combination of theory and computer simulations [4]. The theory was based on the so-called modified mean-field (MMF) approach [5,6], where the problem of interacting magnetic particles is reduced to a oneparticle calculation by defining an effective magnetic field due to the applied field and the interactions with the other particles.…”
Section: Introductionmentioning
confidence: 99%